A Survey of Clinical Usage of Non-steroidal Intra-Articular Therapeutics by Equine Practitioners - Velloso Alvarez, Ana; Boone, Lindsey H.; Braim, Amy Poulin; Taintor, Jenifer S.; Caldwell, Fred; Wright, James C.; Wooldridge, Anne A. (Frontiers in Veterinary Science, 2020)
There are several non-steroidal intra-articular therapeutics (NSIATs) available for use by equine practitioners for the treatment of performance-limiting joint-related pathology. Information is limited on perceived clinical efficacy, recommended treatment protocols, and associated complications. Our objective with this cross-sectional survey was to investigate the current clinical usage of NSIATs by equine practitioners. An electronic cross-sectional convenience survey inquiring about the use of steroidal and NSIATS (platelet-rich plasma, autologous conditioned serum, autologous protein solution, cellular therapies, and polyacrylamide hydrogel) was distributed internationally to equine practitioners. A total of 353 surveys were completed. NSIATs were used by 87.5% of the participants. Corticosteroids and hyaluronic acid remain the intra-articular therapeutic of choice among practitioners, followed by autologous conditioned serum, and platelet-rich plasma and autologous conditioned protein. Polyacrylamide hydrogel was the least used. Practitioners were more likely to use NSIATs if their caseload was greater than 50% equine (P <0.001), they treated more than 10 horses intra-articularly per month (P < 0.001), and horses treated were considered English sport horses (P= 0.02). Years in practice and practice location did not influence the use of NSIATs. One of the most common reasons why NSIATs were chosen was to treat acute articular pathologies. As survey limitations, answers to questions regarding clinical response and complication rates were based on subjective estimation and practitioners recall, not clinical records. In conclusion, corticosteroids remain the most widely used intra-articular therapeutic. Among the NSIATs, blood-based products are more commonly used by practitioners, followed by cellular and synthetic products. Equine practitioners frequently use NSIATs, choosing to treat acute joint pathology more than previously reported.